Biomechanical analysis of front crawl arm stroke and leg kick by tachograph measuring system - Batorova, M.; Motyeka, J.; Sastny, J.; Lepkova, H. (Science, Movement & Health, 2016)
Aim: In our case-study contribution we will present the results of crawl technique measurements with the tachograph measuring method, where we focus on analysing the crawl arms stroke and legs kick. This research aims to present a biomechanical analysis of the crawl legs kick (range, position of legs - the angle of kick, frequency, depth of kick etc.) and how the measured parameters influence the efficiency and speed of crawl legs. Another aim is to present a biomechanical analysis of the crawl arm angles and frequency and their impact on the speed and efficiency of crawl arms swimming techniques. Measurements were performed with six racing swimmers of the Czech national swimming team. A partial aim is also providing information on further developments in measuring techniques with accelerometers at the Brno University of Technology (BUT). Methods: For measurements of swimmers, we used the Tachograph measuring system together with a system of underwater cameras. For processing the results from the tachograph, we used the Swim Data Viewer software, which is part of the measuring system. For measuring angles, we used a video recording program MB-Ruler. For processing of the results, we used Excel, Matlab and for their evaluation, we used linear regression. Results: In the results of our case study of 6 male swimmers from the Czech national swimming team, Hypothesis 1 was confirmed (swimmers with a deeper arm stroke have a higher mean speed). Hypothesis 2 (mean speed is decreasing with decreasing frequency) was not confirmed. Hypothesis 3 (swimmers with a greater angle of arm stroke also have a higher mean speed) was confirmed. Hypothesis 4 (swimmers with a deeper kick have lower mean speed) was not confirmed. Hypothesis 5 (swimmers with a deeper kick have lower efficiency) was not confirmed. For Hypothesis 6, the dependence of mean speed on the frequency was only slightly positive, and thus statistically insignificant. Hypothesis 7 (swimmers with higher frequency of kicks have higher efficiency of crawl legs) was confirmed. Conclusion: Thanks to the results of this case study, the future direction of development research and analysis of swimming techniques will be outlined, the results will be forwarded to swimming coaches in the next phases of research and they will influence the training preparation of the national swimming team of the Czech Republic.